Determinação das caracteristicas de microrganismo probiótico dos microrganismos isolados da bebida de fermentação tradicional caiçuma produzida pelos indígenas da etnia Arara - Lacerda, Adnaldo Junior Brilhante (2017)
Caiçuma is a fermented drink traditionally prepared by Arara Indians. This type of drink, present microorganisms with probiotic activity, being beneficial to the health of the human being. In this work the objective was to determine the probiotic activity of the strains Lactococcus lactis Ri29, Lactobacillus plantarum Ri54, Leuconostoc lactis Ri61 (yellow color), Leuconostoc lactis Ri62 (white color) and Candida tropicalis Ri90, isolated from the caiçuma. For the evaluation of the probiotic activity were performed the tolerance tests at pH 2.0 and bile salts, the hydrolysis capacity of these salts. The degree of cell surface hydrophobicity, autoaggregation and co-aggregation capacity, fermentation capacity of bovine milk and soy milk, amylolytic and proteolytic activities, as well as the antagonism test using strains of Escherichia coli and Staphylococcus aureus and the test of probiotics. All strains showed resistance to pH 2.0 and were tolerant to bile salts. Ri29 and Ri54 had slow growth and Ri61, Ri62 and Ri90 showed pronounced growth in both tests. Ri54, Ri61 and Ri62 produced precipitate corresponding to the hydrolysis of bile salts. In the hydrophobicity test, Ri54 presented the highest value 74.39% and Ri29 the lowest, 26.61%. In the auto-aggregation tests (with the same lineage) and co-aggregation (with Escherichia coli), Ri54 presented values of 62.57% and 38.01% and Ri61 43.44% and 24.59%, respectively. In the co-aggregation in pairs (among the five selected ones), the Ri61Ri62 pair reached 75.31% co-aggregation. As for the antagonism test, Ri90 produced halo of 44.39 mm for Escherichia coli and 39.54 mm for Staphylococcus aureus. Ri54 caused the formation of halos of 31.28 mm and 29.60 mm for the pathogens previously mentioned. In the bovine milk fermentation test, Ri29, Ri54 and Ri61 provided values close to pH 4.0 and Ri62 and Ri90 above pH 5.5. As for soy milk, Ri29, Ri54, Ri61 and Ri90 provided values above pH 5.7 and Ri62 reached pH 4.65. The highest value amylolytic activity was obtained for Ri54, with 20.60 mm and for proteolytic Ri29 was highlighted with 26.25 mm. Ri54 (22.08 mm) and Ri61 (19.97 mm) also presented good values. In the antibiogram test, the strains Ri29, Ri54 and Ri61 showed susceptibility to all antimicrobials. The strains Ri62 and Ri90 showed resistance to Ampicillin, Erythromycin and Penicillin G, and other susceptible antimicrobials. From the tests, it was possible to confirm the probiotic activity of the lines Lactococcus lactis Ri29, Lactobacillus plantarum Ri54, Leuconostoc lactis Ri61 in vitro, being in agreement with the consulted literature.